PENGARUH PENERAPAN CHSE DAN PROMOSI TERHADAP KEPUTUSAN TAMU UNTUK MENGINAP PADA HOTEL SANTIKA - Rangga Anggara; Chelsia Pranindyasari (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2023)
The determination of the Covid-19 pandemic by the World Health Organization and government policies related to the PSBB policy had a major impact on room occupancy rates, this condition caused worry for guests to carry out activities in the hotel area. To prevent a significant decrease in the number of room occupancy rates, the Ministry of Tourism and Creative Economy issued a CHSE guidance program for the hotel industry to ensure that health protocols are in place and provide a sense of security for hotel guests who come, so that guests feel comfortable deciding to stay at the hotel. However, the phenomenon that occurred at Hotel Santika for the 2019- 2021 period was a decrease in the average occupancy from 69% before the pandemic to 43% and fluctuations occurred in the following years. The purpose of this study was to analyze the influence of the implementation of CHSE and promotions on the decision for guests to stay overnight, the data source of this research is primary data derived from samples, namely hotel guests. Data collection used a saturated sample by distributing questionnaires to 109 respondents. Research using multiple linear regression analysis method. The results of this study indicate that; CHSE in guest entrance, lobby front desk, restaurant, rest room & meeting room has a positive effect on the decision to stay and CHSE in the guest room, although the promotion variable does not have a significant effect on the decision to stay of guests at Hotel Santika, because during the pandemic many hotels reduced room prices simultaneously.